An analytical method for solving exact solutions of a nonlinear evolution equation describing the dynamics of ionic currents along microtubules. Issue 6 (1st November 2017) - Alam, Md. Nur; Alam, Md. Mahbub
Abstract: In this article, a variety of solitary wave solutions are observed for microtubules (MTs). We approach the problem by treating the solutions as nonlinear RLC transmission lines and then find exact solutions of Nonlinear Evolution Equations (NLEEs) involving parameters of special interest in nanobiosciences and biophysics. We determine hyperbolic, trigonometric, rational and exponential function solutions and obtain soliton-like pulse solutions for these equations. A comparative study against other methods demonstrates the validity of the technique that we developed and demonstrates that our method provides additional solutions. Finally, using suitable parameter values, we plot 2D and 3D graphics of the exact solutions that we observed using our method.